Respuesta :

Answer:

First rule:

[tex]a_{0} = 9[/tex]

[tex]a_{n+1} = a_{n}-2[/tex]

Second rule:

[tex]a_{n} = 9-2n[/tex] for n = 0,1,2,...

Step-by-step explanation:

First rule:

The first term of the sequence is 9, and for obtaining the next term you subtract 2, then:

[tex]a_{0} = 9[/tex]

[tex]a_{n+1} = a_{n}-2[/tex]

Second rule:

[tex]a_{n} = 9-2n[/tex] for n = 0,1,2,...

Answer:9,7,5,3,”1”

Step by step exclamation:

So it’s subtracting by two. 9-2 = 7!! And it keeps going on until you get the answer!!